Mixed method research on lifelong learning: capturing its dynamics in a multi-generational workforce in the wake of COVID 19. (27th July 2021) - Gupta, Jaya; Misra, Pooja
The coronavirus outbreak has ignited significant disruptions across industries. An agile mindset to assimilate learning into life is mandatory to be able to perform in the redesigned workplace. The pandemic is disrupting the workforce of all the generations. The present mixed-method study seeks to examine the differences in lifelong learning attribute of the prominent generations in the Indian workforce through qualitative, in-depth interviews followed by a more generalisable, quantitative survey. The qualitative interview data of the Phase 1 was analysed using text mining and topic modelling. Based on the topics identified, the quantitative data related to lifelong learning and self-efficacy was gathered in the Phase 2 from the respondents of different generations by questionnaire. The lifelong learning trait differences and drivers of self-efficacy across generational cohorts were analysed by MANOVA followed by a regression analysis. The results suggest that there are major differences across generations.